Neural correlates of autobiographical memory: evidence from a positron emission tomography study in patients with mild cognitive impairment and Alzheimer's disease - Frankenberg, Claudia; Pantel, Johannes; Haberkorn, Uwe; Degen, Christina; Buchsbaum, Monte S.; Herold, Christina; Schröder, Johannes (Frontiers in psychiatry, 2021)
Background: Autobiographical memory (AM) changes are the hallmark of Alzheimer's disease (AD) and mild cognitive impairment (MCI). In recent neuroimaging studies, AM changes have been associated with numerous cerebral sites, such as the frontal cortices, the mesial temporal lobe, or the posterior cingulum. Regional glucose uptake in these sites was investigated for underlying subdimensions using factor analysis. Subsequently, the factors were examined with respect to AM performance in a subgroup of patients.Methods: Data from 109 memory clinic referrals, who presented with MCI (n = 60), mild AD (n = 49), or were cognitively intact, were analyzed. The glucose metabolic rates determined by positron emission tomography (PET) with 18F-fluorodeoxyglucose (FDG) in 34 cerebral sites important for AM were investigated for underlying subdimensions by calculating factor analysis with varimax rotation. Subsequently, the respective factor scores were correlated with the episodic and semantic AM performance of 22 patients, which was measured with a semi-structured interview assessing episodic memories (characterized by event-related emotional, sensory, contextual, and spatial-temporal details) and personal semantic knowledge from three periods of life (primary school, early adulthood, and recent years).Results: Factor analysis identified seven factors explaining 69% of the variance. While patients with MCI and AD showed lower values than controls on the factors frontal cortex, mesial temporal substructures, and occipital cortex, patients with MCI presented with increased values on the factors posterior cingulum and left temporo-prefrontal areas. The factors anterior cingulum and right temporal cortex showed only minor, non-significant group differences. Solely, the factor mesial temporal substructures was significantly correlated with both episodic memories (r = 0.424, p < 0.05) and personal semantic knowledge (r = 0.547, p < 0.01) in patients with MCI/AD.Conclusions: The factor structure identified corresponds by large to the morphological and functional interrelations of the respective sites. While reduced glucose uptake on the factors frontal cortex, mesial temporal substructures, and occipital cortex in the patient group may correspond to neurodegenerative changes, increased values on the factors posterior cingulum and left temporo-prefrontal areas in MCI may result from compensatory efforts. Interestingly, changes of the mesial temporal substructures were correlated with both semantic and episodic AM. Our findings suggest that AM deficits do not only reflect neurodegenerative changes but also refer to compensatory mechanisms as they involve both quantitative losses of specific memories and qualitative changes with a semantization of memories.